Parental leave benefits and child penalties - Sevrin Waights (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
I use the universe of tax returns in Germany and a regression kink design to estimate the impact of the benefit amount available to high-earning women after their first childbirth on subsequent within-couple earnings inequality. Lower benefit amounts result in a reduced earnings gap that persists beyond the benefit period for at least nine years after the birth. The longer-term impacts are driven by couples where the mother earned more than the father pre-birth. Simulations suggest it would take a 50% reduction in the benefit amount to completely eliminate long-run child penalties for sample couples. Lower benefits also reduce take-up of paid leave by mothers, lower the chances of having further children, and have no impact on marital stability.
Keywords: D63; H31; J13; J16; K31; M52; Z13; 330; Child penalties; gender inequality in earnings; social norms; parental leave policy; regression kink design